2008
DOI: 10.1136/ard.2007.086157
|View full text |Cite
|
Sign up to set email alerts
|

Infliximab improves vascular stiffness in patients with rheumatoid arthritis

Abstract: Objectives:Patients with rheumatoid arthritis (RA) have increased cardiovascular mortality. Tumour necrosis factor α (TNFα)-blocking therapy has been shown to reduce RA disease activity measures and joint damage progression. Some observational studies suggest that TNFα blockade reduces mortality and incidence of first cardiovascular events. The mechanisms contributing to these outcomes are unclear. This study assessed the effects of infliximab treatment on vascular stiffness and structure in patients with RA.M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
61
1
4

Year Published

2010
2010
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(73 citation statements)
references
References 42 publications
6
61
1
4
Order By: Relevance
“…Although one recently published study reported that treatment with etanercept reduced AIx, 31 our result is in agreement with the majority of previous investigations exploring the effect of TNF-␣ antagonists on AIx. 11,16,22,32 AIx is a composite measure dependent on the magnitude and site of pulse wave reflection in addition to the speed of the reflected wave. Peripheral vasodilatation is a well-known feature of infectious diseases, such as septicaemiae, induced among others by TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although one recently published study reported that treatment with etanercept reduced AIx, 31 our result is in agreement with the majority of previous investigations exploring the effect of TNF-␣ antagonists on AIx. 11,16,22,32 AIx is a composite measure dependent on the magnitude and site of pulse wave reflection in addition to the speed of the reflected wave. Peripheral vasodilatation is a well-known feature of infectious diseases, such as septicaemiae, induced among others by TNF-␣.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, reports from Swedish and British biological registers indicate that anti-TNF-␣ therapy reduces the incidence of cardiovascular events in patients with RA. 19,20 Moreover, treatment with TNF-␣ antagonists is reported by a few small studies to improve endothelial function and aortic stiffness in patients with RA 11,21,22 and microvascular function in patients with AS. 14 Aortic pulse wave velocity (aPWV), a measure of aortic stiffness, is considered the current gold standard for measuring arterial stiffness.…”
mentioning
confidence: 99%
“…This inhibition has been ascribed to the improvement of insulin resistance (11), endothelial function (12), and arterial wall stiffness (13). Anti-TNF-α blockades are associated with the reduction of carotid intima-media thickness (14), and the induction of hyperadiponectinemia (15).…”
mentioning
confidence: 99%
“…In a post hoc analysis of longitudinal data from a randomized placebo controlled study also showed that infliximab therapy was associated with an improvement of arterial stiffness as measured by pulse wave velocity (PWV), but not carotid IMT and carotid artery plaque, in patients with RA (n=26) [89]. Further, 1-year treatment with anti-TNFα therapy has been shown to improve both PWV and carotid IMT in patients with inflammatory arthropathies [90].…”
Section: Biologics Therapy and Atherosclerosismentioning
confidence: 99%